Using Information and Communication Technologies (ICT) for Mental Health Prevention and Treatment - Fonseca, Ana; Osma, Jorge (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The use of Information and Communication Technologies (ICT) to deliver psychological services has been emerging as an effective way of increasing individual access to mental health promotion, prevention, and treatment. This Special Issue brings together different contributions focusing on the acceptability and feasibility, (cost-)effectiveness, potentialities, and limitations of ICT-based psychological services for mental health promotion, prevention, and treatment. In each paper, the implications for the implementation of ICT tools in different settings (e.g., primary care services) and for future research are discussed.